Effects of Exposure to Physical Factors on Homeopathic Preparations as Determined by Ultraviolet Light Spectroscopy. (2010) - Marschollek, Barbara; Nelle, Mathias; Wolf, Martin; Baumgartner, Stephan; Heusser, Peter; Wolf, Ursula
Abstract : Clinical trials have reported statistically significant and clinically relevant effects of homeopathic preparations. We applied ultraviolet (UV) spectroscopy to investigate the physical properties of homeopathic preparations and to contribute to an understanding of the not-yet-identified mode of action. In previous investigations, homeopathic preparations had significantly lower UV light transmissions than controls. The aim of this study was to explore the possible effects of external factors (UV light and temperature) on the homeopathic preparations. Homeopathic centesimal (c) dilutions, 1c to 30c, of copper sulfate (CuSO4 ), decimal dilutions of sulfur (S8 ), 1x to 30x, and controls (succussed potentization medium) were prepared, randomized, and blinded. UV transmission was measured at six different time points after preparation (from 4 to 256 days). In addition, one series of samples was exposed to UV light of a sterilization lamp for 12 h, one was incubated at 37°C for 24 h, and one was heated to 90°C for 15 min. UV light transmission values from 190 or 220 nm to 340 nm were measured several times and averaged. After each exposure, UV transmission of the homeopathic preparations of CuSO4 was significantly reduced compared to the controls, particularly after heating to 37°C. Overall, the nonexposed CuSO4 preparations did not show significantly lower UV transmission compared to controls; however, the pooled subgroup of measurements at days 26, 33, and 110 yielded significant differences. UV light transmission for S8 preparations did not show any differences compared to controls. Our conclusion is that exposure to external factors, incubation at 37°C in particular, increases the difference in light transmission of homeopathic CuSO4 preparations compared to controls.